How perceived school culture relates to work engagement among primary and secondary school teachers? Roles of affective empathy and job tenure - Fu, Chunhua; Zhao, Zhen; Wang, Huimei; Ouyang, Mingkun; Mao, Xiaoling; Cai, Xiao; Tan, Xinhua (Frontiers in Psychology, 2022)
Evidence suggests that perceived school culture is the most powerful predictor of teachers’ work performance. However, studies to date have paid little attention to the potential mechanisms behind this association. On the basis of the job demands–resources (JD–R) model, the present study explored the mediating role of affective empathy and the moderating role of job tenure in the association between perceived school culture and teachers’ work engagement. 647 primary and secondary school teachers completed questionnaires measuring perceived school culture, affective empathy, and work engagement. After gender and educational level were included as covariates, the results showed that perceived school culture positively correlated with teachers’ work engagement, and more importantly, this association was partially mediated by affective empathy. In addition, job tenure significantly moderated the direct association between perceived school culture and work engagement. Specifically, there was a stronger association between perceived school culture and work engagement for teachers with shorter job tenure than those with longer job tenure. The findings suggested the direct effect of perceived school culture on work engagement, and the indirect effect of perceived school culture on work engagement through the mediating role of affective empathy. These findings enrich our understanding of how perceived school culture associates with work engagement, and highlight the moderating role of job tenure in the direct association between perceived school culture and work engagement.